2017
DOI: 10.1128/aem.02526-16
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Temporal Turnovers of Sediment Bacterial and Eukaryotic Communities in Response to Dredging: Nonresilience and Functional Changes

Abstract: To study the stability and succession of sediment microbial and macrobenthic communities in response to anthropogenic disturbance, a time-series sampling was conducted before, during, and 1 year after dredging in the Guan River in Changzhou, China, which was performed with cutter suction dredgers from 10 April to 20 May 2014. The microbial communities were analyzed by sequencing bacterial 16S rRNA and eukaryotic 18S rRNA gene amplicons with Illumina MiSeq, and the macrobenthic community was identified using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…However, the diversity of microbial communities within sediment samples from highly impacted locations was significantly higher ( p < 0.05) 4 months post-disturbance compared to their pre-disturbance state ( Supplementary Figures S1C,D , Branch 2 and Downstream sites). Other studies in coastal ( Galand et al, 2016 ) and freshwater sediments ( Zhang et al, 2017 ) have also found that disturbance increases diversity in sediment microbial communities. Microbial communities from less or non-impacted sites were relatively stable over the course of the sampling regimen.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, the diversity of microbial communities within sediment samples from highly impacted locations was significantly higher ( p < 0.05) 4 months post-disturbance compared to their pre-disturbance state ( Supplementary Figures S1C,D , Branch 2 and Downstream sites). Other studies in coastal ( Galand et al, 2016 ) and freshwater sediments ( Zhang et al, 2017 ) have also found that disturbance increases diversity in sediment microbial communities. Microbial communities from less or non-impacted sites were relatively stable over the course of the sampling regimen.…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, these results are supported by significant increases in the abundance of taxa associated with nutrients or pollutants from agricultural runoff at highly impacted locations (see Figure 4 above). Other studies have shown that microbial communities may take several years to exhibit resilience to disturbance ( Enwall et al, 2007 ; Allison and Martiny, 2008 ; Zhang et al, 2017 ). In highly impacted areas of chronic contamination such as the Kewaunee River watershed, microbial communities may never return to a “pre-disturbance” state as they are continually exposed to multiple stressors from agricultural land runoff (microbial pathogens, heavy metals, nutrients, antibiotics, etc.).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of aquaculture-induced organic enrichment, this work has focused on foraminifera (Pawlowski et al, 2014(Pawlowski et al, , 2016He et al, 2019) and ciliates (Forster et al, 2018), as well as general analyses of eukaryotic (Chariton et al, 2015) and bacterial communities (Dowle et al, 2015;Fodelianakis et al, 2015;Stoeck et al, 2018;Verhoeven et al, 2018;Moncada et al, 2019). The use of metabarcoding as a monitoring tool has also been explored with reference to localized disturbances caused by dredging (Zhang et al, 2017) and off-shore drilling (Lanzén et al, 2016;Laroche et al, 2017;Frontalini et al, 2020). These studies have shown that bacterial and eukaryotic metabarcoding analyses can serve as sensitive methods to detect anthropogenic impacts on sediment habitats, including both short-term responses and longterm effects on community resilience and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have correlated water column and/or sediment geochemical variables with metabarcoding data (Pawlowski et al, 2014;Chariton et al, 2015;Dowle et al, 2015;Fodelianakis et al, 2015;Lanzén et al, 2016;Forster et al, 2018;He et al, 2019;Moncada et al, 2019), there is a lack of research on this topic involving cross-comparisons of prokaryotic and eukaryotic communities. In cases where both types of metabarcoding analyses have been employed, shifts in community structure have either not been correlated with geochemical data or only a limited set of measurements has been used (La Rosa et al, 2001;Zhang et al, 2017;Keeley et al, 2018;Stoeck et al, 2018). Addressing this absence of information, therefore, is essential to establishing a full understanding of how metabarcoding can be best employed as a tool for marine ecosystem monitoring.…”
Section: Introductionmentioning
confidence: 99%